Half-Life of a Zealot - Hunt, Swanee (Book collections on Project MUSE., 2006)
"Much of Swanee Hunt's professional work is geared toward promoting inclusion, particularly by expanding women's roles in shaping public policy and encouraging the participation of all stakeholders in peace processes across the globe. The foundation that Hunt established in 1981 has contributed more than fifty million dollars to cultivate progressive social change at local, national, and international levels."--Jacket